Impacto da exposição perigestacional a uma dieta rica em sacarose sobre o desenvolvimento precoce de disfunções metabólicas na prole de ratas Wistar - SOUZA, Ivana Letícia Santos (2022)
The prevalence of metabolic diseases in children and adolescents is increasing rapidly and significantly, being pointed out by the World Health Organization as one of the biggest public health problems in the world. The expressive growth of these pathologies is mainly related to changes in the behavior of society in general, which started to consume diets with a high content of added sugars (sucrose) and ultra processed foods, in addition to the increase in sedentary lifestyle. In this context, the DOHaD concept aims to elucidate how punctual changes that occur early in developing organisms can result in late metabolic alterations and an increased risk of chronic diseases in adult life. Taking these aspects into account, the aim of this study is to investigate the impact of excessive exposure to added sugars during pregnancy and lactation on the onset and early progression of metabolic syndrome in offspring. For this purpose, adult Wistar female rats (n = 15), with approximately 75-90 days of life, were divided into two groups: those exposed to nutritional stress (n = 7) and those that were not exposed (n = 8). This nutritional stress was through a diet containing 25% sucrose (DRS) compared to a control diet, which contained 10% sucrose (CTR). After the 7-week induction period the rats were mated with age-matched rats (n=15) and pregnancy confirmed from the morning vaginal smear. The rats continued with their respective diets (CTR or DRS) throughout pregnancy and lactation. At the birth of the pups, the offspring was adjusted to 8 pups per rat, due to the mother's breastfeeding contribution. At 21 days of age, the pups were weaned and separated from their mothers and divided into two experimental groups: the CTR group (offspring of males and females of the mothers fed with CTR diet during pregnancy and lactation) and the DRS group (offspring of males and females of the mothers fed with DRS diet during pregnancy and lactation). All offspring animals were fed with a CTR diet ad libitum from weaning and were equally followed up to 30 days of life, when euthanasia occurred. The calculation of the Lee Index and glucose tolerance test were performed, in addition to blood collection for biochemical analysis and key-organs for morphometry and histology. From these procedures, it can be stated that the main result obtained was the significant impairment in the DRS offspring's glycolipid homeostasis, through glucose intolerance, hypertriglyceridemia, hypercholesterolemia and the significant increase in TyG, which indicates the beginning of the development of type 2 diabetes mellitus and the consequent establishment of the metabolic syndrome as early as during the late childhood of these animals. In addition, there was the significant increase in steatosis, inflation and ballooning in the liver of experimental animals, which culminated in steatohepatitis, the predecessor stage of hepatocellular cancer. Finally, it is concluded that the period of pregnancy and lactation are a metabolic window susceptible to nutritional stresses and metabolic reprogramming of offspring, and that this reprogramming occurs differently between sex.